2017
DOI: 10.3390/biom7030045
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Functional Amyloids from Fungi: Surface Modification by Class I Hydrophobins

Abstract: Class I hydrophobins produced from fungi are amongst the first proteins recognized as functional amyloids. They are amphiphilic proteins involved in the formation of aerial structures such as spores or fruiting bodies. They form chemically robust layers which can only be dissolved in strong acids. These layers adhere to different surfaces, changing their wettability, and allow the binding of other proteins. Herein, the modification of diverse types of surfaces with Class I hydrophobins is reported, highlightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The good surface activity and exceptionally high surface elasticity of HFBs makes them the most surface-active proteins currently known, which promoted their successful Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 9:00 AM exploitation in several different fields. Some of the uses proposed for HFBs include stabilization of foams and emulsions in the food industry [16], biotechnological applications such as drug delivery [17,18], biomedical imaging [19] and coatings for biomedical devices [20], but also use as dispersing agents [21,22] and intermediates for surface immobilization of proteins [23,24] and polymers [25]. The ability of HFBs to self-assemble at oil-water interfaces and stabilize oil droplets makes them potential candidates for a more efficient and greener EOR strategy, also in consideration of the fact that the potential for large scale production of these proteins has been shown in industrial operations for both classes of HFBs [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The good surface activity and exceptionally high surface elasticity of HFBs makes them the most surface-active proteins currently known, which promoted their successful Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 9:00 AM exploitation in several different fields. Some of the uses proposed for HFBs include stabilization of foams and emulsions in the food industry [16], biotechnological applications such as drug delivery [17,18], biomedical imaging [19] and coatings for biomedical devices [20], but also use as dispersing agents [21,22] and intermediates for surface immobilization of proteins [23,24] and polymers [25]. The ability of HFBs to self-assemble at oil-water interfaces and stabilize oil droplets makes them potential candidates for a more efficient and greener EOR strategy, also in consideration of the fact that the potential for large scale production of these proteins has been shown in industrial operations for both classes of HFBs [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to utilizing the knowledge gained from studies of surface proteins in therapeutics, we also have to be open to alternate uses for these discoveries. For example, numerous reports suggest that the hydrophobins can be used to coat surfaces for both biomedical and industrial applications due to their unique properties as functional amyloids [13, 48]. In conclusion, conidial surface proteins play an integral role at the interface between normal fungal function and pathogenesis while offering a wealth of potential biomarkers and novel therapeutic targets.…”
Section: Surface Proteins Have Potential Biomedical and Industrial Apmentioning
confidence: 99%
“…In addition to the role of the rodlet layer in fungal life during conidiogenesis and conidial dispersal in the air, it has been shown that rodlets have a role in fungal–host interactions and favor the pathogenic behaviour of fungal pathogens in mammals, plant and insect hosts ( Aimanianda et al, 2009 , Talbot et al, 1996 , Zhang et al, 2011 ) or play a positive role during plant symbiosis ( Whiteford and Spanu, 2002 ). Moreover, due to their specific physicochemical properties, hydrophobins have potential for numerous biotechnological applications ( Piscitelli et al, 2017 , Wösten and Scholtmeijer, 2015 , Zhao et al, 2009 ). Their coating properties could be used to functionalize metals and plastic or carbon nanotubes in order to prevent the formation of bacterial biofilms or to immobilize enzymes on surface ( Tanaka et al, 2017 ) or to stabilize pharmaceutical emulsions and facilitate drug delivery ( Artini et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%